The oro-dental phenotype in Prader–Willi syndrome: a survey of 15 patients - ISABELLE BAILLEUL-FORESTIER (IAPD and Blackwell, 2008)
Prader–Willi syndrome (PWS) is a complex disorder characterized by severe neonatal hypotonia and feeding problems, childhood-onset hyperphagia and obesity, short stature, facial dysmorphy, hypogonadism, and learning and behavioural difficulties 1 . It is a rare disorder caused by genetic defects in certain regions of chromosome 15q11–13, including paternal interstitial deletion, maternal uniparental disomy and imprinting defect 2 . The prevalence of PWS is estimated to be 1 in every 26 000 live births 3 . Oro-facial manifestations reported in PWS include almond-shaped eyes with up-slanting palpebral fissures and a triangular mouth (Figs 1 and 2).